2000
DOI: 10.1021/jp002319b
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Charge Separation and Recombination in a Novel Methanofullerene−Triarylamine Dyad Molecule

Abstract: Intramolecular charge separation (CS) and charge recombination (CR) processes of the dyad molecule linking C 60 and N,N-di(6-tert-butylbiphenyl)benzenamine (BBA) were investigated by pico-and nanosecond laser flash photolysis methods. Furthermore, intermolecular electron transfer to a methanofullerene (C 61 H 2 ) was also investigated; the electron-transfer rate between triplet excited C 61 H 2 and BBA was somewhat slower than that of C 60 due to less negative reduction potential of C 61 H 2 . As for the BBA-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 48 publications
6
97
3
Order By: Relevance
“…S13b †), but gave longer lifetime (950 ps and 2000 ps at 712 nm), presumably because of the lower solvent polarity. 50 Consequently, the transient absorption result, together with the static and time-resolved fluorescence data, are indicative of photoinduced electron transfer and suggest that 1 serves as electron acceptor in the 1-SWCNT donor-acceptor system.…”
Section: Time-resolved Fluorescence and Nanosecond Transient Absorptimentioning
confidence: 85%
“…S13b †), but gave longer lifetime (950 ps and 2000 ps at 712 nm), presumably because of the lower solvent polarity. 50 Consequently, the transient absorption result, together with the static and time-resolved fluorescence data, are indicative of photoinduced electron transfer and suggest that 1 serves as electron acceptor in the 1-SWCNT donor-acceptor system.…”
Section: Time-resolved Fluorescence and Nanosecond Transient Absorptimentioning
confidence: 85%
“…54,55 Since bisbiphenylaniline (N,N-bis(biphenylyl)aniline; BBA) is a very good electron donor with respect to 1 C 60 *, several studies of BBAspacerC 60 molecules have been reported as shown in Figure 32. 56,57 One of the merits of the study of BBAspacerC 60 molecules is the sharp and intense absorption As for short molecular wires, a comparison between the phenylvinyl (PV) linkage (compound 30) and the phenylethynyl (abbreviated as phenylacetyl and PA) linkage (compound 31) is possible for ferrocene (Fc) as electron donor (Figure 33). 59,60 The R CC value for (FcPA) 2 C 60 is larger than that of (FcPV) 2 C 60 ; thus, the observed k S CS values decrease with the length of the bridges.…”
Section: ¹1mentioning
confidence: 99%
“…[12] This property renders C 60 useful as a building block in artificial-light-harvesting and energy-conversion systems. [13][14][15][16] Non-covalently linked electron-donor-acceptor hybrids that are based on coordinating C 60 to porphyrins or phthalocyanines exhibit a number of advantages, such as their flexible and easy synthesis as well as their ability to monitor through-bond versus throughspace electron-transfer interactions.…”
Section: Introductionmentioning
confidence: 99%